Sigmoid Volvulus in An Adolescent Female With Colitis: A Rare Case Report - Jaya Putra, Edwin Satya; Setiawati, Rosy (SCRIPTA SCORE Scientific Medical Journal, 2024)
Introduction: Sigmoid volvulus among pediatric patients is a rare occurrence. Case: A 13-year-old pediatric female presented to hospitalâ€™s emergency department with abdominal pain, nausea, and inability to defecate for three days. No fever or vomiting was reported. She had a multiple episodes of constipation and was menstruating. Physical examination suggested bowel obstruction. Plain abdominal radiograph showed diffuse colon dilation with minimal small bowel and pelvic gas. Abdominal contrast CT revealed severe large bowel dilatation with redundancy from the cecum to the rectosigmoid area, along with a "whirl sign" as the diagnostic feature. Colon in-loop procedure revealed stenosis at the sigmoid-descending colonic junction due to volvulus with partial obstructive ileus. The diagnosis of sigmoid volvulus was confirmed and subsequently the patient underwent an endoscopic decompression procedure. Colitis was visualized during endoscopy. Symptoms completely resolved the following day and her parents requested discharge two days after the procedure.Â  Discussion: Sigmoid volvulus is a potential differential diagnosis in children with symptoms of bowel obstruction. Physicians and radiologists should remain vigilant to avoid morbidity and mortality resulting from delayed and untreated cases. Conclusion: Thorough clinical, radiological, and histopathologic investigations play a crucial role in preventing treatment delays. It is important to be aware of uncommon causes of abdominal pain in the pediatric age group. Keywords: decompression, pediatric, radiology, rare case, sigmoid volvulus Latar Belakang: Volvulus sigmoid pada pasien anak merupakan kasus yang jarang. Presentasi Kasus: Remaja perempuan berusia 13 tahun datang ke Instalasi Gawat Darurat rumah sakit dengan keluhan nyeri perut, mual, dan tidak dapat buang air besar sejak tiga hari yang lalu. Keluhan demam dan muntah disangkal. Terdapat riwayat konstipasi berulang serta pasien saat ini sedang menstruasi. Pemeriksaan fisik mengarah adanya obstruksi saluran cerna. Foto polos abdomen menunjukkan adanya dilatasi kolon difus dengan gas minimal di usus kecil dan area pelvis. CT-scan abdomen dengan kontras menunjukkan dilatasi kolon signifikan disertai adanya redundansi dari sekum hingga area rektosigmoid dan tampak â€œwhirl signâ€ sebagai fitur diagnostik yang sensitif. Hasil colon-in-loop menunjukkan adanya stenosis pada area pertemuan antara kolon sigmoid dan kolon desenden akibat volvulus dengan ileus obstruksi parsial. Diagnosis volvulus sigmoid ditegakkan dan pasien menjalani prosedur dekompresi endoskopi setelahnya. Kolitis tervisualisasi saat prosedur. Keluhan membaik seluruhnya pada keesokan hari dan orang tua pasien meminta pasien dipulangkan dua hari post-prosedur. Diskusi: Volvulus sigmoid merupakan diagnosis diferensial yang potensial pada anak dengan gejala obstruksi saluran cerna. Klinisi dan radiolog harus selalu waspada demi menghindari morbiditas dan mortalitas akibat kasus yang lambat maupun tidak tertangani. Kesimpulan: Pemeriksaan fisik, radiologis, serta histopatologis yang menyeluruh memainkan peranan penting dalam mencegah keterlambatan penanganan. Kasus ini menekankan pentingnya kewaspadaan terhadap suatu penyebab tidak umum kasus nyeri perut pada populasi anak. Â